2015
DOI: 10.3109/09513590.2015.1086513
|View full text |Cite
|
Sign up to set email alerts
|

Association between anti-chlamydial immunity and IVF outcome

Abstract: Background: Elevated antibody titers to Chlamydia trachomatis are detected in up to 70% of women with tubal factor infertility (TFI). In order to evaluate the influence of past chlamydial infection on the results of IVF treatment, a prospective cohort study was performed. Materials and methods: A total of 242 women with TFI were enrolled in the study. Serum samples (n ¼ 242) and follicular fluid (n ¼ 197) were analyzed using enzyme-linked immunosorbent assay for anti-C. trachomatis IgG, IgA, IgM and anti-chlam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…In contrast to other reports [9][10]26], in our center study, there was no statistical evidence of association between ectopic pregnancy and background factors (age, infertility duration, history of ectopic pregnancy), BMI, and parameters of ovarian stimulation. Aspects of the transfer technique (injection pressure, volume, location of the catheter tip), postulated to be contributing factors of EP occurrence, are unified in our practice, thus, could not be evaluated.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to other reports [9][10]26], in our center study, there was no statistical evidence of association between ectopic pregnancy and background factors (age, infertility duration, history of ectopic pregnancy), BMI, and parameters of ovarian stimulation. Aspects of the transfer technique (injection pressure, volume, location of the catheter tip), postulated to be contributing factors of EP occurrence, are unified in our practice, thus, could not be evaluated.…”
Section: Discussioncontrasting
confidence: 99%
“…Even excluding the study with the most weight and patient population [9] (possibly effecting the results) the RR remained similar: RR ¼ 0.9, 95%CI: 0.60-1.37, random effect model. Furthermore, the elimination of articles reporting data from national registers [15,17,18] did not influence the results: RR ¼ 0.82, 95%CI: 0.49-1.37, random effect model.…”
Section: Meta-analysismentioning
confidence: 89%
See 2 more Smart Citations
“…Infection with Chlamydia trachomatis is an important sexually transmitted condition related to tubal infertility with increased salpingitis episodes that leads to tubal blockage [1][2][3]. Many studies revealed that serologic evidence of previous Chlamydia infection is exceptionally related to tubal infertility [4][5][6][7][8] and also decreased the success rate of a positive outcome for in vitro fertilization (IVF) [9]. The individuals with positive serology to chlamydia are at higher risk of developing the pelvic inflammatory disease (PID) [10,11].…”
Section: Introductionmentioning
confidence: 99%